Analisis Pengelolaan Pengaduan Masyarakat di Kantor Badan Pemeriksa Keuangan Perwakilan Provinsi Gorontalo - Feriyanto K Tuna; Irawaty Igirisa; Sry Yulyanty Mozin (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This study aims to determine and analyze the management of public complaints at the Office of the Supreme Audit Agency of Gorontalo Province Representative. This research uses a qualitative research approach. The method used in this research is descriptive qualitative. The data collection techniques used are observation, interviews and documentation. The results showed that the management of public complaints in the Office of the Gorontalo Provincial Representative of the Supreme Audit Agency, the application of the principles of public complaints management, namely Quality Improvement, Accessibility, Transparency, Responsibility (Accountability) and Privacy and Confidentiality have been realized properly, these principles have been carried out in accordance with Standard Operational Procedures and applicable laws and regulations. Of the several principles that have been realized, there are still principles that are not well implemented, namely the principles of Openness to Receive Complaints (Open Disclosure) and Commitment (Commitment). In the principle of Openness to Receive Complaints (Open Disclosure) with the limited topics of complaints that can be complained about by the public, this refers to the limitation of the scope of the problem to be conveyed and used as material for complaints in making complaints, which is the main factor that is a shortcoming in the application of this principle. In addition, the principle of Commitment is still poorly applied by public complaints management employees, especially the commitment to publish the results of public complaints.